Assessment of consent models as an ethical consideration in the conduct of prehospital ambulance randomised controlled clinical trials: a systematic review - Armstrong, Stephanie; Langlois, Adele; Laparidou, Despina; Dixon, Mark; Appleton, Jason P.; Bath, Philip M.W.; Snooks, Helen Anne; Siriwardena, A. Niroshan (BioMed Central, 2017)
Background